Anti-inflammatory effect of hydroalcoholic extract of hibiscus rosa on acute and chronic inflammation - verma, Pankaj; Sharma, Swati; Kumar, Vikas; Chaudhary, Hema (International Journal of Pharmacology and Toxicology, 2016)
Background: The present study was carried out to explore the efficiency of Indian herbal source from Hibiscus rosa against a chronic inflammatory disease. Hibiscus rosa belongs to Malvaceae, acts by suppression of inflammation mediators.Methods: Hydroalcoholic extract form Hibiscus rosa is prepared through soxhlet extraction and Diclofenac is used as the standard. Carrageenan and formaldehyde are administered to induce acute and chronic inflammation. Animals are divided into 6 groups with 6 animals each including Normal group, inflammatory control group, Diclofenac treated group and Hibiscus rosa treated group at different doses of 250 mg/kg, 500 mg/kg and 1000 mg/kg.Results: Different concentrations of Hibiscus rosa treated groups i.e. 250 mg/kg (p<0.05), 500 mg/kg (p<0.05) and 1000 mg/kg (p<0.01) showed significant reduction in Paw edema as compared to controls. Significant reduction in Body weight was also observed in Hibiscus rosa treated groups. Hematological profiles of Hibiscus rosa treated group are satisfying and significant.Conclusion: Results showed significant anti-inflammatory effect of Hydroalcoholic extract of Hibiscus rosa and justifying its therapeutic role in inflammatory condition..